2022
DOI: 10.20360/langandlit29606
|View full text |Cite
|
Sign up to set email alerts
|

Critical Literacy in Canada: A Systematic Review of Curricula and Literature

Abstract: Critical literacy is a pedagogy that serves to mediate social justice issues and educate for transformative social action. We present a systematic review of how critical literacy has been incorporated in Canada’s provincial/territorial curriculum documents since the late 1990s and integrated in K-12 classrooms in the last decade. Our analysis shows that critical literacy has been addressed with varying degrees of explicitness in curricula, and there is an imbalance of studies on critical literacies among provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…CCL is defined as the ability to read and write critically and creatively about sociocultural, political, and social action issues (Luke, 2000(Luke, , 2012. Kaya et al, (2022) confirmed that critical literacy is an educational service to facilitate social justice issues mapping and transform them into social action. Their analysis of critical literacy in Canada recommends integrating critical literacy across curricula.…”
Section: Introductionmentioning
confidence: 97%
“…CCL is defined as the ability to read and write critically and creatively about sociocultural, political, and social action issues (Luke, 2000(Luke, , 2012. Kaya et al, (2022) confirmed that critical literacy is an educational service to facilitate social justice issues mapping and transform them into social action. Their analysis of critical literacy in Canada recommends integrating critical literacy across curricula.…”
Section: Introductionmentioning
confidence: 97%